An assessment of an intentionally designed US summer research program that integrates Deaf, hearing, and sign language interpreting students in chemical research - Harsh, Joseph A.; Hughey, Chrisi A.; Sumner, Isaiah; Wright, Nathan T.; Cobb, Isobel; Thiry, Frances; Rogerson, Anneliese; McGehee, Emma; Stacy, Ashlynn; Sprouse, Savannah; Dovan, Trinity (Frontiers in Education, 2025)
Participation in undergraduate research experiences have been shown to positively influence the learning, development, and educational and career trajectory of students, particularly for individuals from groups traditionally excluded from science, technology, engineering, and mathematics (STEM) fields. As few studies have explored the engagement of deaf and hard-of-hearing (DHH) researchers in inclusive laboratory experiences, this article reports on the assessment of a long-standing summer program that draws on best practices to integrate DHH, hearing, and sign language interpreting students in chemical research. To assess outcomes associated with participation, mixed survey data were collected from student researchers over three consecutive program years. Findings highlight the positive impact of the program for all participants, particularly how the experience contributed to hearing students’ awareness of Deaf culture and inclusive communication strategies. While this case study highlights a model for a unique student group, the general lessons learned are broadly applicable to creating inclusive laboratory environments for researchers of varying abilities and how participation in such experiences may benefit mainstream students’ cultural competences as future practitioners in science disciplines.